Around the world [biomedical engineering in Vietnam]. - Webster, J. (IEEE Engineering in medicine and biology magazine)
The Ho Chi Minh City University of Technology has a biomedical engineering curriculum requiring 42 courses. Students began in 2002 so there have been no graduates. The Can Tho University College of Technology has no training program in biomedical engineering but carries out biomechanics research.